Concurrent feature based design and manufacturing - Suresh Agarwal. (2009)
This thesis addresses the issue of communicating manufacturing information to a design model in a CAD system as the model is being developed or modified. The information is utilised to check if an object being designed is manufacturable by the methods within the manufacturing knowledge domain. This is a key part in the life cycle of product development in what is known today as concurrent engineering.